2016
DOI: 10.3233/cbm-150555
|View full text |Cite
|
Sign up to set email alerts
|

The small leucine rich proteoglycan fibromodulin is overexpressed in human prostate epithelial cancer cell lines in culture and human prostate cancer tissue

Abstract: The expression of fibromodulin was higher in prostatic cancer cells (cell-lines and human tissue) than in normal/benign prostatic cells. Additional studies are required to determine the biological and clinical significance and whether this proteoglycan has a role in carcinogenesis of the prostate or in prostate cancer related inflammatory processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Elevated expression of FMOD has been associated with several types of cancer (Mayr et al, 2005; Reyes et al, 2016), and differential expression of FMOD has been observed in other pathophysiological conditions as well. Yet little was known about the molecular and cellular mechanisms by which FMOD expression is regulated, and only one study has been reported which suggested that FMOD transcription in glioma cells is positively regulated by the TGF-β1/SMAD2 pathway by an epigenetic mechanism (Mondal et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated expression of FMOD has been associated with several types of cancer (Mayr et al, 2005; Reyes et al, 2016), and differential expression of FMOD has been observed in other pathophysiological conditions as well. Yet little was known about the molecular and cellular mechanisms by which FMOD expression is regulated, and only one study has been reported which suggested that FMOD transcription in glioma cells is positively regulated by the TGF-β1/SMAD2 pathway by an epigenetic mechanism (Mondal et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In a carcinoma model, FMOD controls the stoma matrix structure which affects the internal and external fluid stability of the carcinoma stroma (Oldberg et al, 2007). FMOD was suggested to be a tumor-associated antigen in chronic lymphocytic leukemia (CLL) (Mayr et al, 2005); in clinical samples obtained from prostate cancer patients, significant variations of FMOD expression were observed between benign and malignant tissues (Reyes et al, 2016); and a recent study implicated FMOD in glioma cell migration (Mondal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that the SLRP fibromodulin has discrete expression among PC and benign tissues [ 58 ]. PC tissues express this PG, as do PC cell lines with, interestingly, the highest expression determined in the androgen-sensitive human metastatic prostate adenocarcinoma LNCaP clone [ 59 ]. Moreover, the glypican-1 expression in urine cell sediments was proposed as a possible positive marker for PC [ 60 ].…”
Section: Proteoglycan Expression In Hormone-dependent Cancermentioning
confidence: 99%
“…Tumour cells release growth factors and angiogenic factors which play a crucial role in tumour progression, angiogenesis and LVI. Lymphatic endothelial cells, in turn, interact with tumour cells, resulting in the secretion of small leucine-rich repeat proteoglycan, thus stimulating tumour cells to metastasise [13, 14]. However, the key molecular mechanisms underlying LVI, whether the alterations are in the tumour cells, in the endothelial cells or in both remain to be deciphered.…”
Section: Introductionmentioning
confidence: 99%